MICROPROPAGATION OF POTATO (Solanum tuberosum L.) cv. GRANOLA IN LIQUID MEDIUM USING AERATION SYSTEM FOR G0 SEED PRODUCTION - Karyanti (Jurnal Bioteknologi dan Biosains Indonesia, 2022)
Disease-free potato seeds of high quality can be obtained via in vitro culture. The use of liquid medium during in vitro cultures might boost the number of plantlets produced, however, the problem of hyperhydricity in plantlets was often encountered. This study aimed to investigate effects of different sucrose concentrations and application of aeration system on micropropagation of potato cv. Granola using liquid medium. Aseptic nodal explants with 3-4 nodes from established in vitro cultures were subjected to MS liquid medium with a factorial treatment of three sucrose concentrations (0, 7.5, 15 g. L-1) and two culture (with and without aeration). The results showed that MS medium with 7.5 g L-1 sucrose was the best medium to produce the highest number of shoots and nodes. Furthermore, it was found that application of aeration system in MS liquid culture decreased plantlet hyperhydricity and increased the number of shoots, number nodes, plantlet height, as well as improved plantlet morphology and vigor. Application of the aeration system in liquid medium produced 200-230 new potato plants per bioreactor in the acclimatization stage and an average of 2773.5 G0 mini tubers.